Plexiform Neurofibroma of Face: A Challenge for Plastic Surgeons - Muhammad Ahmad; Saleem A. Malik (Journal of the Dow University of Health Sciences, 2009)
Plexiform neurofibroma is a benign tumour of peripheral nerves and connective tissue. They develop most often in patients with neurofibromatosis type 1 (NF1) and often grow continuously. Removal of plexiform neurofibromas is usually unsatisfactory because the network-like growth of these tum ours often invo lv es m u ltip le nerve fascicles and other ad jacen t tissu es. We present an interesting case of Plexiform Neurofibroma involving right half of the face. Surgical excision and debulking of the tissues were performed alongwith the correction of orbital skeleton and facial contours.